The monetary policies of the European Central Bank and the euro's (mal)performance: a stability-oriented assessment - Jörg Bibow (Levy Economics Institute of Bard College, 2001)
The stability-oriented macroeconomic framework established in the Maastricht and Amsterdam Treaties on European Union (TEU), especially the unparalleled status of independence and peculiar mandate of the European Central Bank (ECB), were promised to virtually guarantee price stability and a strong euro. Actual developments have shattered these hopes in a rather drastic way. Despite the dismal monetary developments, conventional wisdom holds that neither the Maastricht regime nor the ECB might possibly be at fault. Yet, the euro's performance over 2000-01 is generally seen as a puzzle. This paper assesses the ECB's role in relation to the euro's (mal-) performance, explores the institutional setting and traditions behind the ECB's conduct, and scrutinizes the rationale that inspired its interest rate policies.
Keywords: 330